Fraud Triangle dan Kecurangan Laporan Keuangan Dengan Model Beneish M-Score - Novi Indriani; Abdul Rohman (Universitas Katolik Soegijapranata Semarang, 2022)
AbstractThe purpose of this study is to provide empirical evidence of the effect of risk factors on the detection of fraudulent financial reporting using the fraud triangle theory. The risk of fraudulent financial reporting is reflected in financial targets, financial stability, the nature of the industry, and auditor turnover as suggested by the Beneish M-Score model. The sample was selected from companies belonging to the consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. By using a purposive sampling method, as many as 99 firm observations are available for further examination. Multiple linear regression analysis is used to test the hypotheses. The results show that financial stability and the nature of the industry have a positive and significant effect on financial statement fraud. However, financial targets and auditor turnover have no effect on fraudulent financial reporting. The results of this study are useful for stakeholders, such as potential investors, investors, creditors, auditors, or other parties, in detecting financial statements that contain fraud, especially those triggered by financial stability and the nature of the industry.AbstrakPenelitian ini bertujuan untuk memberikan bukti empiris pengaruh risiko terhadap pendeteksian kecurangan pelaporan keuangan menggunakan teori segitiga kecurangan. Risiko kecurangan pelaporan keuangan tercermin dalam target keuangan, stabilitas keuangan, sifat industri, dan pergantian auditor seperti yang disarankan oleh model Beneish M-Score. Sampel dipilih dari perusahaan yang termasuk dalam industri barang konsumsi yang terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2020. Sebanyak 99 observasi perusahaan tersedia untuk pengujian hipotesis. Analisis regresi berganda menunjukkan bahwa stabilitas keuangan dan sifat industri berpengaruh positif dan signifikan terhadap kecurangan laporan keuangan. Namun, target keuangan dan pergantian auditor tidak berpengaruh pada pelaporan keuangan yang curang. Hasil penelitian ini bermanfaat bagi pemangku kepentingan, seperti calon investor, investor, kreditur, auditor, atau pihak lain, dalam mendeteksi kecurangan laporan keuangan, terutama yang dipicu oleh stabilitas keuangan dan sifat industri.